The Role of Profit Perception, Firm Capital and Investment Knowledge on Intention to Invest in Sharia Stocks - Magdalena Magdalena; Maryani Wirawan (Journal of Social Science and Business Studies, 2023)
This study aims to determine the effect of firm capital, profit perception, and investment knowledge on intention to invest. This study uses a quantitative approach. The objects in this study are Firm Capital, Profit Perception, and Investment Knowledge for the variable Intention to Invest. The sample in this study amounted to 72 respondents using a questionnaire as a means of measuring data through the Whatsapp group. The analysis technique in this study used the SPSS on multiple linear analysis. The results of this study indicate that the Firm Capital variable has a significant effect on the Intention to Invest with a calculated t value greater than t table. Profit Perception significantly affects the Interest in Investing with a t count greater than t table. The Investment Knowledge Variable significantly influences the Intention to Invest with a t count greater than t table. While the variables Firm Capital, Profit Perception, and Investment Knowledge affect the Intention to Invest simultaneously. So it can be concluded that there is an influence between the variables Firm Capital, Profit Perception, and Investment Knowledge on Intention to Invest.